Intervention effectiveness in reducing the clustering of non-communicable disease risk factors in the workplace: A quasi-experimental study. - Nahla Guesmi; Sihem Ben Fredj; Nawel Zammit; Rim Ghammam; Imed Harrabi; Firas Chouikha; Maher Maoua; Jihen Maatoug; Hassen Ghannem (PLoS ONE)
Understanding the clustering patterns of non-communicable disease risk factors is important to address chronic diseases effectively, thus minimizing their onset and enhancing overall health. This study aimed to assess the feasibility and efficacy of a three-year workplace intervention in decreasing clustering of non-communicable disease risk factors in employees. A quasi-experimental study, including six companies, was conducted in the governorate of Sousse between 2010 and 2014. It involved an intervention group (Sousse-Jawhara and Sousse-Erriadh) and a control group (M'saken). The sample of participants in both groups was representative. Actions promoting physical activity, healthy diet, and smoking cessation in the workplace were included in this intervention. The participants' socio-demographic characteristics and data concerning the risk factors were collected through interviews using a pretested questionnaire. The clustering of tobacco use, physical inactivity, unhealthy diet, obesity, and high blood pressure were examined pre- and post-intervention. In the intervention group, the mean risk factors per employee decreased significantly from 1.99 ± 1.00 to 1.81 ± 1.05 (p < 10-3). A minor non-significant increase, from 1.72 ± 0.97 to 1.78 ± 1.11, was noted in the control group. In the intervention group, the prevalence of two risk factor clusters dropped significantly from 40% to 34.4% pre- and post-intervention (p = 0.014). However, a non-significant decline was noted in the control group. Combinations such as obesity/hypertension and unhealthy diet/physical inactivity tended to aggregate in both groups. Overall, the intervention program showed significant protective effects in reducing the co-occurrence of multiple risk factors in the intervention group, with an adjusted OR of 0.81; CI95% [0.68-0.97]. Along with the existing literature, the present study confirmed the feasibility and effectiveness of health promotion programs in reducing non-communicable disease risk factors and their clustering. Integrating this intervention program into a national health policy could potentially generalize its positive impact.